Speed governor design for synchronous machine - Chua, Roger Yu Ding. (2009)
In the current setup of the Intelligent Energy Distribution System (IEDS), speed governor is essential to control the frequency and real power output. In the laboratory, the speed of the prime mover is controlled manually. An electronic controller can replace the manual work by varying the DC voltage applied to the field winding of a separately excited DC motor. By controlling the speed of the DC motor through a speed governor, we are able to control the frequency of the system. This report present the components and equipment used through the final year project. Operational amplifiers, RC circuit, phase angle module as well as half controlled bridge rectifier were used. A software, PSIM, is used to simulate the results of the proposed design of speed governor. Theoretical calculations were done and compared with the simulation results to ensure that they are approximately the same. After verifying the performance using simulation, hardware testing is done. In IEDS, the main controlling device is the Automatic Gen-set Controller (AGC). AGC identify the load requirements and operating at the most economical way. Interfacing with the Automatic Gen-set Controller (AGC) allowed the user to control the speed governor. Different setting can be input to AGC for different purposes. Different scenarios were tested on the speed governor to evaluate the performance of the speed governor. They included isolated generator with and without load as well as synchronizing with grid with and without load.